2019
DOI: 10.1038/s41598-019-55359-5
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing and the feasibility of manual gene annotation: A pilot study in the nematode Pristionchus pacificus

Abstract: Nematodes such as Caenorhabditis elegans are powerful systems to study basically all aspects of biology. Their species richness together with tremendous genetic knowledge from C. elegans facilitate the evolutionary study of biological functions using reverse genetics. However, the ability to identify orthologs of candidate genes in other species can be hampered by erroneous gene annotations. To improve gene annotation in the nematode model organism Pristionchus pacificus, we performed a genome-wide screen for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 63 publications
(93 reference statements)
0
35
0
Order By: Relevance
“…Therefore, we used the information about the predicted domains, RNA-seq data generated in this study, and Illumina and PacBio RNA-seq datasets generated earlier [26,95,96] to manually reannotate the NHR gene predictions in P. pacificus. We submitted the improved annotations to http://wormbase.org as part of a larger set of manually curated gene annotations [97]. For the tree of CAP domains in P. pacificus and P. fissidentatus, we predicted domains in the Pinocchio versions of gene predictions for both genomes [60] and selected genes that contained "PF00188" as a predicted PFAM domain.…”
Section: Phylogenetic Reconstructionsmentioning
confidence: 99%
“…Therefore, we used the information about the predicted domains, RNA-seq data generated in this study, and Illumina and PacBio RNA-seq datasets generated earlier [26,95,96] to manually reannotate the NHR gene predictions in P. pacificus. We submitted the improved annotations to http://wormbase.org as part of a larger set of manually curated gene annotations [97]. For the tree of CAP domains in P. pacificus and P. fissidentatus, we predicted domains in the Pinocchio versions of gene predictions for both genomes [60] and selected genes that contained "PF00188" as a predicted PFAM domain.…”
Section: Phylogenetic Reconstructionsmentioning
confidence: 99%
“…In our previous study, we focused on the identification of missing one-to-one orthologous genes in the P. pacificus genome and the identification of artificial fusions between two adjacent P. pacificus genes both of which have one-to-one orthologous genes [23] . Here, we aim to further improve the quality of one-to-one orthologous genes by finding and curating P. pacificus genes that are either unusually large and or small with regard to their C. elegans counterpart.…”
Section: Protein Length Comparison Of Orthologs Identify Hundreds Of mentioning
confidence: 99%
“…We obtained 8,348 one-to-one orthologs between C. elegans and P. pacificus that were predicted based on best reciprocal BLASTP hits in a previous study [23] . We then calculated the protein length ratio between the P. pacificus and C. elegans one-to-one orthologs.…”
Section: Candidate Identification Based On Length Comparison Of Orthomentioning
confidence: 99%
See 1 more Smart Citation
“…This would be valuable even when applied to only a single species, preferably one with a near-complete genome, which can then be used as a template to re-evaluate gene models of other oomycetes and train gene predictors. Especially community-based annotation would be a powerful resource (Rödelsperger et al, 2019 Reliable functional annotation of the predicted proteome is an additional prerequisite for identifying the fundamental components of genome-scale models. In Chapter 2, we performed an automated proteome annotation for 42 oomycete species, which revealed that the large majority of predicted proteins could not be assigned to a KEGG orthologous group (KO), which are protein ortholog clusters with validated functions (Mao et al, 2005).…”
Section: From Genome Sequence To Genome-scale Metabolic Modelmentioning
confidence: 99%